Optimization of postural control in precise gaze shifts and laser pointing - Bonnet, Cédrick T.; Dubrulle, Déborah; Barela, José A. [UNESP]; Defebvre, Luc; Delval, Arnaud (Elsevier, 2021)
Young adults are known to reduce their postural sway to perform precise visual search and laser pointing tasks. We tested if young adults could reduce even more postural and/or center of pressure sway to succeed in both tasks simultaneously. The methodology is novel because published pointing tasks usually require continuously looking at the pointed target and not exploring an image while pointing elsewhere at the same time. Twenty-five healthy young adults (23.2 ± 2.5 years) performed six visual tasks. In the free-viewing task, participants randomly explored images with no goal. In two visual search tasks, participants searched to locate objects (easy search task) or graphical details (hard search task). Participants additionally pointed a laser beam into a central circle (2°) or pointed the laser turned off. Postural sway and center of pressure sway were reduced complementarily – in various variables – to perform the visual search and pointing tasks. Unexpectedly, the pointing task influenced more strongly postural sway and center of pressure sway than the search tasks. Overall, the participants adopted a functional strategy in stabilizing their posture to succeed in the pointing task and also to fully explore images. Therefore, it is possible to inverse the strength of effects found in the literature (usually stronger for the search task) in modulating the experimental methodology. In search tasks more than in free-viewing tasks, participants mostly rotated their eyes and head, and not their full body, to stabilize their posture. These results could have implications for shooting activities, video console games and rehabilitation most particularly.
Keywords: Ecological images on a large display; Interaction and priority; Postural control; Visual and pointing tasks; Young adults